STUDI TATA LETAK KETERANGAN (LABEL) DISPLAY PAMERAN DI MUSEUM TEKSTIL JAKARTA: STUDY OF THE LAYOUT OF EXHIBITION DISPLAY LABELS IN THE TEXTILE MUSEUM JAKARTA - Charles S Marpaung; Anita Armas; Agus Adhityatama (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
The Indonesian Textile Museum is one of the museums in Jakarta that stores thousands of collections of Nusantara wastra. The Textile Museum functions as a place to preserve, store, exhibit, and publicize wastra or ancient fabrics from various regions, and become a means of education for visitors to get to know traditional Indonesian fabrics. In order for information about traditional fabrics in the Textile Museum to be conveyed well to visitors, one of the factors that play an important role is the layout of the museum display information (label). Labels on exhibition displays have an important role because they become a bridge of communication between the products on display and the visitors who see. Therefore, the layout of the display information must be taken seriously, by applying ergonomics, anthropometry, and typography factors. This study aims to determine the label layout system on displays at the Textile Museum, associated with the application of ergonomics, anthropometry, and typography factors. The method used is descriptive qualitative with ergonomics and anthropometry approach to analyze the display label layout system. The results showed that the position of the product description label had not fully applied ergonomic and anthropometric factors, as well as the selection of fonts and sizes that caused the product description to be less legible.